Interleukin-4 receptor alpha is still required after Th2 polarization for the maintenance and the recall of protective immunity to Nematode infection. - Justin Komguep Nono; Hlumani Ndlovu; Nada Abdel Aziz; Thabo Mpotje; Lerato Hlaka; Frank Brombacher (Public Library of Science (PLoS), 2017)
There is currently no vaccine against parasitic nematodes and the knowledge on the mechanisms by which protective immunity against this class of parasites is achieved is continuously expanding. Nematode parasites trigger a host protective type 2 immune response via interleukin-4 receptor alpha (IL-4Rα). Despite this central role, it is not known whether IL-4Rα has a role in maintaining host type 2 immune responses following polarization. To determine the role of IL-4Rα after polarization, we used a recently established strain of rosaCreERT2-/+IL-4Rα-/Lox mice where il4rα gene deletion can be temporally controlled. We show that sustained expression of IL-4Rα is required for the maintenance of type 2 immune responses and protective immunity following interruption after polarization with Nippostrongylus brasiliensis primary infection. Moreover, we show by temporal deletion of IL-4Rα prior to secondary infection with N. brasiliensis that signaling via this receptor drives more efficient recall of type 2 immune responses and clearance of the parasites. Together, this study demonstrates that sustained IL-4Rα mediated signaling is required for the maintenance of anti-nematode type 2 immune responses, describing a novel function for IL-4Rα that is distinct from its role in immune polarization.